A public health ethics framework for the older community - Laetus Lategan; Gert Van Zyl; Willem Kruger (Koers : Bulletin for Christian Scholarship)
An ethical framework for dealing with geriatric communities is mostly absent in developing countries. This article presents an ethics framework for public health that can be used to address older persons' communities and their associated vulnerability. A mixed methods approach was used for the design of this framework. A principal component analysis was employed to summarise the information content. The rotated component matrix identified nine determinants from the survey outcome. A five-point Likert scale rated fifty statements relevant to care for older persons. The rating of the mentioned statements confirmed that social determinants influence older persons' health. Furthermore, such statements' ratings also highlighted the role of government and support systems in the care of older persons. The evident link between social determinants and ethics was noteworthy, as well as the fact that social determinants contribute towards ethical challenges. It was further confirmed that an ethical framework could contribute towards health and judgements concerning older communities.